The Reality of Technology Incubators as a Mechanism to Enhance The Pillars of the Knowledge Economy in Saudi Arabia» An Applied Study of the Badir Technology Incubators - Osman, Anjom; Zeyada, Rania (The Arab Journal of Administration, 2021)
Given that the crucial element for the success of technology incubators (i.e. incubators that help ICT and tech innovators convert their ideas into tangible goods) largely lies in enhancing the services they provide (financial, administrative, technical, accounting, consulting and information, legal, logistics) and that the diagnosis and analysis of the reality of tech incubators is a way to help improve such services by identifying the obstacles and challenges facing tech incubators, the overall objective of this study is, therefore, to examine the reality of the Badir Program tech incubators by obtaining an insight into the level of the services provided by the program incubators, the role they play in strengthening the pillars of the knowledge economy, and the challenges and obstacles facing the projects incubated by the program from the perspective of the incubated entrepreneurs. This is achieved through an applied study of all the Badir incubators in Saudi Arabia which incubate 329 technical projects. The research sample consisted of 222 entrepreneurs. The research findings show that the consulting and information services are the most important services provided by the Badir tech incubators and the most important obstacles are the lack of preparation of budgets and financial forecasts for the projects and the lack of funding commensurate with the nature of them. Moreover, the pillars of HR development and support for technology and communication activities are the most important pillars of the knowledge economy that the program incubators enhance. Lastly, a number of significant recommendations have been reached that can help to improve the quality of the services provided by the tech incubators, including creating links between innovators and project funders, paying attention to mechanisms for marketing technology products, to qualifying those involved in the administration of the incubators and to community outreach on the program incubators, creating links between the program incubators and global research centers and establishing risk departments within the incubators to protect incubated technical projects from running into difficulties and failure.